Laguange Loss and Imperialism in the Play Translations by Brian Friel - Azizah, Aisyah Nurul; Syauki, Sheryll Rania Faradillah; Rangkuti, Rahmadsyah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2023)
The play Translation explores the impact of British colonial rule on the Irish language and culture. The play is set in 19th-century Ireland, and it vividly depicts the struggles faced by a group of characters as they navigate the challenges of translating Irish place names into English, showcasing the complex dynamics between language, power, and identity. It seeks to provoke critical thinking, raise awareness, and advocate for the preservation of linguistic diversity, cultural identity, and the rights of indigenous communities affected by language loss and imperialism. This research uses a qualitative descriptive research method. The researchers collected the data from the script and interpreted it using discourse analysis. It is found that language loss in the context of imperialism is a consequence of the imposition of a dominant language and the devaluation of indigenous languages.